Family skill development for attention deficit hyperactivity disorder behavior problem alleviation model in at-risk preschool children: a mixed methods study - Khamenkan, Kanokjun; Homchampa, Pissamai (Jurnal Ners, 2024)
Introduction: Attention Deficit Hyperactivity Disorder is the most prevalent childhood mental health problem. This study examined families caring for children with ADHD and created a model to alleviate behavior problems in at-risk preschoolers. Methods: This exploratory sequential mixed-methods study comprised two phases. Phase 1 included a qualitative retrospective survey that examined family experiences in caring for ADHD children. This involved in-depth interviews with 14 family caregivers (FCGs) and utilized thematic content analysis. Phase 2 involved creating, implementing, and evaluating a family skill development model using a quasi-experimental design. Thirty FCG- ADHD at-risk preschool child dyads, utilizing services at two Child Development Clinics, were paired and equally divided into experimental and control groups. Data analysis used repeated measures ANOVA and covariances (ANCOVA). Results: The study FCGs reported that family-child interactions and positive parenting alleviated the ADHD at-risk preschool child's behavior problems. The Family Skill Development for ADHD Behavior Problem Alleviation Model was constructed and validated. Results from within-group comparisons showed significant improvements in the experimental group, with reduced behavior problems (p<0.05, Î·p2=0.28) in ADHD at-risk children, improved caregiver behaviors to alleviate the child's behavior problems (p<0.01, Î·p2=0.37), and enhanced family functions (p< 0.001, Î·p2=0.42). Conclusions: The model significantly aids families in alleviating behavior problems in ADHD at-risk children, improving family functions and caregivers' efforts to address the children's behavioral issues. It is a promising parental intervention model for fostering healthy families and reducing behavior problems in ADHD-at-risk preschool children in northeastern Thailand and similar contexts.